(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Basic immunization is an effective preventive measure to protect infants and toddlers from various preventable diseases. However, mothers of toddlers still lack optimal understanding and awareness regarding the importance of basic immunization, potentially affecting adherence to the immunization schedule. This community service activity aims to increase the knowledge and awareness of mothers of toddlers and integrated health post (Posyandu) cadres through basic immunization education in the Pagar Merbau Community Health Center (Puskesmas) work area. The activity was implemented through health education using interactive lectures and discussions, supported by leaflets and posters as a means of conveying information. Evaluation was conducted by comparing the level of knowledge of participants before and after the educational activity. The community service results showed a significant increase in participants’ understanding. Before the education, only about two participants had good knowledge of basic immunizations, but after the education, that percentage increased to 10 out of 15 participants. This improvement was evident in their understanding of immunization, its benefits, the types of basic immunizations, and the accuracy of the immunization schedule. The increase in knowledge was seen in the understanding of the definition of immunization, its benefits, types of basic immunization, and the accuracy of the immunization schedule. In addition, there was an increase in the active participation of Posyandu cadres in providing information and motivation to mothers of toddlers regarding the importance of immunization. Basic immunization education has proven effective as a community service strategy in increasing the knowledge and awareness of mothers of toddlers and integrated health post (Posyandu) cadres, so it is hoped that it can contribute to increasing compliance and completeness of basic immunization in infants and toddlers in the working area of ​​the Pagar Merbau Community Health Center.